Cytokine dysregulation in children with cerebral palsy. (13th November 2020) - Zareen, Zunera; Strickland, Tammy; Fallah, Lida; McEneaney, Victoria; Kelly, Lynne; McDonald, Denise; Molloy, Eleanor J
Abstract : Aim: To examine pro‐ and anti‐inflammatory cytokines in children with cerebral palsy (CP) at baseline and in response to endotoxin (lipopolysaccharide), and correlate outcomes compared with age‐matched comparisons, to evaluate their ability to mount an immune response. Method: Serum cytokines were assessed in 12 children (eight males, four females; mean age 10y 1mo [SD 1y 8mo], 6–16y) with CP against 12 age‐matched comparisons (eight males, four females; mean age 9y 1mo [SD 1y 1mo]). Pro‐ and anti‐inflammatory cytokines (interleukin‐1β, interleukin‐2, interleukin‐6, interleukin‐8, interleukin‐10, interleukin‐18, tumour necrosis factor [TNF]‐α, TNF‐β, interferon‐γ, granulocyte‐macrophage colony‐stimulating factor [GM‐CSF], vascular endothelial growth factor [VEGF], erythropoietin, and interleukin‐1 receptor antagonist) were measured at baseline and in response to in vitro simulation with lipopolysaccharide by multiplex enzyme‐linked immunosorbent assay. Results: Significantly higher erythropoietin was found at baseline in children with CP compared with the comparison group. There was a strong response to lipopolysaccharide for interleukin‐8, VEGF, TNF‐α, and GM‐CSF in both children with CP and the comparison group; however, there was significant lipopolysaccharide hyporesponsiveness in children with CP compared with the comparison group for interleukin‐1α, interleukin‐1β, interleukin‐2, and interleukin‐6. Interpretation: Altered cytokine responses in children with CP compared with the comparison group demonstrate an altered inflammatory state that may contribute to ongoing sequelae and could be a target for therapy. What this paper adds: Altered inflammatory responses persist in children with cerebral palsy (CP). Erythropoietin is elevated in children with CP compared with the comparison group. Children with CP have reduced interleukin‐1α, interleukin‐1β, interleukin‐2, and interleukin‐6 inflammatory responses to lipopolysaccharide. What this paper adds: Altered inflammatory responses persist in children with cerebral palsy (CP). Erythropoietin is elevated in children with CP compared with the comparison group. Children with CP have reduced interleukin‐1α, interleukin‐1β, interleukin‐2, and interleukin‐6 inflammatory responses to lipopolysaccharide. This article is commented on by Schleiss on pages 365–366 of this issue.